Effects of Visually Induced Motion Sickness on Emergency Braking Reaction Times in a Driving Simulator. (September 2019) - Reinhard, René; Tutulmaz, Ender; Rutrecht, Hans M.; Hengstenberg, Patricia; Geissler, Britta; Hecht, Heiko; Muttray, Axel
Objective: The study explores associations of visually induced motion sickness (VIMS) with emergency braking reaction times (RTs) in driving simulator studies. It examines the effects over the progression of multiple simulated drives. Background: Driving simulator usage has many advantages for RT studies; however, if it induces VIMS, the observed driving behavior might deviate from real-world driving, potentially masking or skewing results. Possible effects of VIMS on RT have long been entertained, but the progression of VIMS across simulated drives has so far not been sufficiently considered. Method: Twenty-eight adults completed six drives on 2 days in a fixed-base driving simulator. At five points during each drive, pedestrians entered the road, necessitating emergency braking maneuvers. VIMS severity was assessed every minute using the 20-point Fast Motion Sickness Scale. The progression of VIMS was considered in mixed model analyses. Results: RT predictions were improved by considering VIMS development over time. Here, the relationship of VIMS and RT differed across days and drives. Increases in VIMS symptom severity predicted more prolonged RT after repeated drives on a given day and earlier within each drive. Conclusion: The assessment of VIMS in RT studies can be beneficial. In this context, VIMS measurements in close temporal proximity to the behaviors under study are promising and offer insights into VIMS and its consequences, which are not readily obtainable through questionnaires. Application: Driving simulator–based RT studies should consider cumulative effects of VIMS on performance. Measurement and analysis strategies that consider the time-varying nature of VIMS are recommended.